Numerical Modeling of a Hot Plate Stove for Peanut Roasting - Anthony Agyei-Agyemang; Michael Kweku Commeh; Peter Oppong Tawiah; Benjamin Atribawuni Asaaga (Journal of Engineering)
Heat treatment, especially roasting, is known to reduce harmful fungal species and mycotoxin formation to a great extent. Experiments were conducted for heat treatment and the effects of introducing different fin configurations. ANSYS Fluent 14.5 was used to simulate the three-dimensional (3D) roaster geometry. The effect of the addition of different fins at the bottom of the hot plate was then studied. It was observed that maximum surface temperatures of 133°C, 153.25°C, 310.63°C, and 265.07°C were obtained after 180 minutes (three hours) for the experimental (without fins), predicted (without fins), predicted (with rod fins), and predicted (with honeycomb fins), respectively. The addition of honeycomb and rod fins to the roster’s plate increased temperatures by 115.34% and 143.03% of the original roaster hot plate. Thus, a design with rod fins added to the hot plate could improve its thermal performance and hence reduce the harmful effects of possible fungal species and mycotoxin contamination.